The aesthetic mind philosophy and psychology - Schellekens, Elisabeth; Goldie, Peter (Oxford : Oxford University Press, 2011)
This title breaks ground in bringing together empirical sciences and philosophy to enhance our understanding of art and the aesthetic. An eminent international team of experts explores the roles of emotion, imagination, empathy, and beauty in this realm of human experience, discussing visual and literary art, music and dance.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Aesthetics; Art -- Philosophy